PORIM International Palm Oil Congress - Malaysia. Palm Oil Research Institute (Bangi : Palm Oil Research Institute of Malaysia, 1999)
Contains the papers that has been presented on PORIM International Palm Oil Congress
System requirements: Hardware requirements, PC with a 20 MHz - 386 processor, 2 Mb RAM, 16 colour VGA, hard disc and a mouse. The program requires 3.6 MB free disc space software requirements; windows format on 3.5' HD disc for usse on stand alone PC's or PC networks. PC DOS 3.3 and windows 3.0 or lawter versions.
Keywords: Palm oil industry -- Malaysia -- Congresses; Palm oil -- Marketing -- Malaysia -- Congresses